Teacher reflections and praxis: a case study of Indian teachers of English as a foreign language - Makarani, Sakilahmed A. R. (University of Hawai'i at Mānoa, 2012)
This case study engaged Gujarati English as Foreign Language (EFL) teachers in video-based reflection with the goal of increasing their reflective abilities and uncovering their understandings about reflective teaching practices in the Indian pedagogical and cultural context. The study aimed to explore, and gain a deeper understanding of how structural, institutional, and social dynamics of the larger socio-political cultural context of India affected the classroom teachers' thinking and their teaching practices. It was hoped that not only would the Gujarati teachers demonstrate an ability to reflect on their practice, but that they would also engage in a critical examination of the factors that impacted their context. The computer-based qualitative data analysis software, Atlas.ti, was used to analyze data using a grounded theoretical approach. The findings indicated that participants successfully engaged in reflection about their teaching using video as the tool for their professional development. Initially teacher participants had mixed feelings about recording and watching videos of their classroom instruction; however, teacher participants later enjoyed the experience, explicitly stating that such reflection helped them. The study also revealed that teacher participants perceived parental, social, institutional, and economic factors as influences on their students' learning, however these were simply identified as problems or conditions without any type of deeper critical analysis. Further, it was found that the teachers did not reach a critical level of reflection, nor did they consider taking action to address fundamental contextual issues. While this study showed that teacher reflection using digital video recordings of classroom practice can be a productive approach to meaningful teacher reflection in India, the study also demonstrated that teachers need specific exposure to deeper critical pedagogical thinking to go beyond simply identifying or blaming the social or economic issues embedded in their context. The study concludes with recommendations on how to reach critical teacher reflection. It is hoped that this case study will add to the growing body of research literature related to teacher self-reflection as a means to improving teaching practice and preparing teachers to take on social challenges in the Indian context. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
ISBN: 9781303035289 Pages: 173 Publication Title: ProQuest LLC Loc in Archive 1697502591; ED554753 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1697502591?accountid=9851 KerkoCite.ItemAlsoKnownAs: 2339240:NZ8XTVSM 2339240:ZZQBKRNI 2405685:FMI8USWB 2405685:V48XT6S6 2534378:C6KXYQA7 2534378:IW3DL8F8
Keywords: Case Studies; Computer Software; Cultural Context; ERIC; Resources in Education (RIE); Economic Factors; English (Second Language); Foreign Countries; Grounded Theory; India; Indians; Language Teachers; Qualitative Research; Reflective Teaching; Second Language Instruction; Second Language Learning; Social Influences; Teacher Attitudes; Teaching Methods; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096525; __finaldtb

The Impact of ICT as Another Route to Overcome Learning Barriers for Students with SEN: A Case Study in an Egyptian Context - Al-Gawhary, Wedad; Kambouri, Maria (International Association for the Development of the Information Society, 2012)
The purpose of this case study was to measure the impact of using ICT in Individual Learning Programmes of students with learning disabilities. Twenty five students and thirteen teachers took part in the research which was based on classroom observations. The Kappa coefficient was employed as a measure to statistically quantify the students' acquisition and progress in learning computer and literacy skills through raters' observations. A high correlation between Keyboard, PowerPoint, and literacy skills (writing, reading, and maths) was revealed suggesting the significance and impact of keyboard training as an essential component towards achieving educational objectives. Moreover, thematic analysis of the teachers' interviews provided a further dimension for understanding factors influencing the ICT integration process. These results further confirmed the positive impact of computer skills training on the students' learning experience which also revealed a strong belief in the right of every child to all learning opportunities, particularly ICT regardless of his/her abilities.(Contains 2 tables.) [For the complete proceedings, "Proceedings of the International Association for Development of the Information Society (IADIS) International Conference on Cognition and Exploratory Learning in Digital Age (CELDA) (Madrid, Spain, October 19-21, 2012)," see ED542606.]
Publication Title: International Association for Development of the Information Society KerkoCite.ItemAlsoKnownAs: 2339240:95DQ5J33 2405685:M5TD7M7N
Keywords: Autism; Barriers; Case Studies; Cerebral Palsy; Communications; Computer Literacy; Computer Mediated Communication; Computer Software; Down Syndrome; Foreign Countries; Heterogeneous Grouping; Information Technology; Interrater Reliability; Mixed Methods Research; Semi Structured Interviews; Semitic Languages; Special Needs Students

A case study of using an online community of practice for teachers' professional development at a secondary school in China - Wang, Qiyun; Lu, Zhiping (Learning, Media and Technology, 2012)
In this case study, an online community was designed at a secondary school in China for the teachers to prepare their lessons collectively, reflect on their teaching practices, collect comments from peers, and share resources. A survey was administered to the teachers to investigate their perceptions on the online community for their professional development. Two hundred and eighty-three teachers responded to the survey and eight teachers were further interviewed by email. The result showed that most teachers liked using the online community as they could gain subject knowledge and could obtain support from peers, share experiences and get feedback, and exchange resources. Also, online entries confirmed that transformational changes in teaching pedagogy and students' learning activities occurred along the time. However, certain teachers did not participate in the online community frequently. This paper describes the context of the case study, design dimensions of the online community, teachers' positive perceptions on using the online community, and transformational changes. Also, strategies for promoting effective use of the online community are discussed and follow-up studies to address the challenges involved in this study are proposed. [PUBLICATION ABSTRACT]
Place: Basingstoke Publisher: Taylor & Francis Ltd. Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1240554543?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.685077 2339240:IW35GJG8 2405685:5KA76IR7 2405685:5UJZ5TUP 2534378:7P96MCEU 2534378:I2ZKMFEE 2534378:TEPS99BX
Keywords: Case Studies; China; Communities of Practice; Distance Education; ERIC; Current Index to Journals in Education (CIJE); Education–Teaching Methods And Curriculum; Educational Practices; Electronic Learning; Electronic Mail; Foreign Countries; Interviews; Learning; Lesson Plans; Mail Surveys; Online instruction; Participant Satisfaction; Pedagogy; Polls & surveys; Professional Development; Professional development; Secondary Education; Secondary School Teachers; Secondary school teachers; Teacher Surveys; Teaching Methods; Technology Uses in Education; Transformative Learning; __:import:01; __:match:final; __:matched; __:study_id:2096477; __finaldtb; community of practice; lesson planning; professional development; reflection; technology

Online learning community: A case study of teacher professional development in Indonesia - Sari, Eunice (Intercultural Education, 2012)
This paper investigates the concept of online learning community (OLC) to address the issues of teacher professional development practice in twenty-first-century Indonesia. Teachers in Indonesia are trained in a 'conventional way', hence, not ready to prepare the younger generations for entrance into the twenty-first-century complex life and work environment. The pedagogical transformation of a teacher can be facilitated through teacher professional development. Recent studies show that OLC holds great promise in improving teachers' professional practice. This paper presents key results of the introduction and trialling of OLC with Indonesian teachers and teacher educators between 2009 and 2010 and aims to explore the feasibility of this model to support professional development of teachers in this era. The social learning interactions among community members were examined using Scardamalia's Twelve Socio-Cognitive Determinants of Knowledge Building and Hoftsede's Cultural Dimension Review for Indonesia.
KerkoCite.ItemAlsoKnownAs: 10.1080/14675986.2012.664755 2339240:L9YC4RVC 2405685:W2R874SP

Digital mismatch: Expectations and realities of digital competency amongst pre-service education students - Duncan-Howell, Jennifer (Australasian Journal of Educational Technology, 2012)
Pre-service education students entering university can be categorised broadly into two distinct groups, those who are coming directly from secondary school and those who are not. The second group can be quite diverse, ranging in age, academic and/or work experience. However, what both of these groups share is a digital expectation and they expect upon completion of their studies to be more digitally fluent than when they entered university, they expect to be taught via a range of digital technologies and they expect to use their digital skills throughout their personal and professional lives. These expectations have been either largely ignored or have failed to be understood by universities, resulting in a mismatch between student expectations and their experiences. However, the teaching staff within universities may be ill-prepared to meet these demands, either due to being non-users or exhibiting the same or lower levels of digital fluency as their students. The mismatch between student expectations and the reality is highlighted by an empirical case study involving undergraduate students enrolled in pre-service education degrees at an Australian university. The study will present clear evidence that students' digital expectancy should be considered when planning and improving learning environments.
Number: 5 zotzenLib.CopiedFrom: 2339240:2CK7YFH8 KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.819 2339240:2CK7YFH8 2405685:JM9PRADZ

The iPad as a Tool For Education - a case study - Heinrich, P. (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:FC3GMYB8 2405685:YGDJMN4F

iPad in education: A case study of iPad adoption and use in a primary school. - Henderson, S., & Yeow, J. (In 45th International Conference on System Science (HICSS) 2012, 2012)
00000 KerkoCite.ItemAlsoKnownAs: 2129771:8UWM3IZS 2405685:YVTIBQYU
Keywords: ⛔ No DOI found

Assessing the policy influence of research: A case study of governance research in Viet Nam - Pellini, Arnaldo; Anderson, James H; Tran, Huong Thi Lan; Irvine, Renwick (Overseas Development Institute, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:F58FH7TK 2405685:QTTE2VHQ

Check my school: A case study on citizen's monitoring of the education sector in the Philippines - Shkabatur, Jennifer (World Bank Group, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:KC39FKTL 2405685:Q3BVDSZZ

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M. Mahruf C.; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers’ teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers’ professional development. Using the case of a pre-pilot intervention in the Underprivileged Children’s Educational Programs schools, it explores the teachers’ professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers’ professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Publisher: Routledge _eprint: https://doi.org/10.1080/13664530.2012.668103 KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2012.668103 10/gf5f6p 2339240:QYT78QZJ 2405685:AJFFY6AZ 2534378:EYTQ9C76 2534378:ILM8S5MC 2534378:L6R23M7S 2534378:PXRSVU2M 2534378:TBRE94GM 2534378:U2JMZZFP
Keywords: AUDIOVISUAL education; BANGLADESH; Bangladesh; COMPUTER assisted instruction; ENGLISH language – Study & teaching – Foreign speakers; Education–Teaching Methods And Curriculum; Educational technology; LANGUAGE teachers; Learning; PROFESSIONAL education; Professional development; SECONDARY school teachers; TEACHER development; TEACHERS – Attitudes; Teacher education; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2099954; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; teachers’ professional development; technology-enhanced learning

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.
Num Pages: 18 Publication Title: ActionAid KerkoCite.ItemAlsoKnownAs: 2339240:4FGB56K3 2405685:53CECDLI

Blended learning for academic resilience in times of disaster or crisis - Mackey, Julie; Gilmore, Fiona; Dabner, Nicki (Journal of Online Learning and Teaching, 2012)
Blended learning can provide academic resilience in times of natural disaster, civil emergency, and crisis. While blended pedagogies are widely used in tertiary settings, very little has been written about the role of blended learning in times of crisis, or the pedagogical challenges of rapid course redesign to mitigate disruptive circumstances. This case study describes the immediate post-earthquake challenges of redesigning courses using different blends of face-to-face and online activities to meet the needs of on-campus, regional campus, and distance pre-service teacher education students. The research question asked, "What can be learned from the experiences of academic staff directly involved in the adaptation and redesign of blended courses in a time of disaster?" This descriptive case study employed quick-response research strategies to gather time-sensitive data while it was fresh in the minds of the participants. This article discusses key findings and concludes with recommendations to assist program and course leaders to prepare in advance for resilient blended learning in times of natural disaster, crisis, and emergency.
KerkoCite.ItemAlsoKnownAs: 2339240:DTZGGJX5 2405685:8GAX8R3I

School-based teachers' professional development through technology-enhanced learning in Bangladesh - Mahruf C Shohel, M; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers' teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers' professional development. Using the case of a pre-pilot intervention in the Underprivileged Children's Educational Programs schools, it explores the teachers' professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers' professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Place: Abingdon Publisher: Taylor & Francis Ltd. shortDOI: 10/gf5f6p KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2012.668103 10/gf5f6p 2405685:NA7NT9BB 2534378:EYTQ9C76
Keywords: Bangladesh; Education–Teaching Methods And Curriculum; Educational technology; Learning; Professional development; Teacher education; UCEP-Bangladesh; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; technology-enhanced learning

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR10.100 2339240:B8RGF7UM 2405685:ZSVGWH7J

Assessing user acceptance toward blog technology using the UTAUT model - Pardamean, Bens; Susanto, Mario (International Journal of Mathematics and Computers in Simulation, 2012)
Blogs are among the many commonly used technologies for education and learning. They are also both conversational technologies and constructivist learning tools. Their interactive, collaborative, user-friendly, and instant archival features have transformed blogs into effective tools for enhancing case-based teaching methods in the asynchronous nature of the online environment. This study investigated the student populace’s acceptance of the blog technology through the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. UTAUT integrates eight theories from social psychology and sociology in order to examine the effects of major factors on behavioral intention and actual use of blog to learn e-business course materials and topic discussions. The results showed that both social influence and performance expectancy had a significant relationship with behavioral intention, whereas effort expectancy did not. In this study, behavioral intention did not have a significant relationship with actual usage level of blogs as a learning tool.
KerkoCite.ItemAlsoKnownAs: 2339240:QX33CKMX 2405685:QDHQ7BL5
Keywords: ⛔ No DOI found

Planning and designing educational technology for low-income communities: A participatory and proactive approach - Ezumah, Bellarmine (Disruptive Technologies, Innovation and Global Redesign: Emerging Implications, 2012)
This chapter is an excerpt of a study that addressed the above concern using the One Laptop Per Child (OLPC) projects in Nigeria and Ghana as a case. It also situates the OLPC XO-laptop as a disruptive technology, because it aims at altering the existing pedagogy of the communities in which it was introduced through its constructivist approach. Moreover, as with most disruptive technologies, the XO laptop project is considered revolutionary, dramatically cheaper than regular laptops, convenient, and provides a different kind of learning content. As with the theme of this chapter, the XO laptop, although possessing disruptive technological qualities, was unable to achieve its goal due to lack of thorough planning and implementation of the adoption process. Results from the study informed the author to posit a model for technology adoption in low-income communities that is considered inclusive, participatory, and proactive, involving all stakeholders in setting up a policy. Such policy is expected to serve as benchmark for measuring the congruency of any proposed product whether disruptive or sustainable to the local need before its adoption.
KerkoCite.ItemAlsoKnownAs: 10.4018/978-1-4666-0134-5 2339240:RRTECR3A 2405685:8K8CRIHL
Keywords: ___working_potential_duplicate

Planning and designing educational technology for low-income communities: A participatory and proactive approach - Ezumah, Bellarmine (Disruptive Technologies, Innovation and Global Redesign: Emerging Implications, 2012)
This chapter is an excerpt of a study that addressed the above concern using the One Laptop Per Child (OLPC) projects in Nigeria and Ghana as a case. It also situates the OLPC XO-laptop as a disruptive technology, because it aims at altering the existing pedagogy of the communities in which it was introduced through its constructivist approach. Moreover, as with most disruptive technologies, the XO laptop project is considered revolutionary, dramatically cheaper than regular laptops, convenient, and provides a different kind of learning content. As with the theme of this chapter, the XO laptop, although possessing disruptive technological qualities, was unable to achieve its goal due to lack of thorough planning and implementation of the adoption process. Results from the study informed the author to posit a model for technology adoption in low-income communities that is considered inclusive, participatory, and proactive, involving all stakeholders in setting up a policy. Such policy is expected to serve as benchmark for measuring the congruency of any proposed product whether disruptive or sustainable to the local need before its adoption.
KerkoCite.ItemAlsoKnownAs: 10.4018/978-1-4666-0134-5.ch017 2339240:6SLEALNK 2405685:GQ3B44QV
Keywords: ___working_potential_duplicate

Life planning by digital storytelling in a primary school in rural Tanzania - Duveskog, Marcus; Tedre, Matti; Sedano, Carolina Islas; Sutinen, Erkki (Educational Technology & Society, 2012)
Storytelling is one of the earliest forms of knowledge transfer, and parents often use it for teaching their children values and knowledge. Formal schooling, however, is less inclined to use storytelling as a vehicle for knowledge transfer, and even less as a vehicle for modern self-directed, student-centered, and constructionist pedagogy. Research literature reports experiences on student-centered storytelling in schools, but there is little information about such learning environments using modern information technology. Using a case study approach, we collected qualitative data from a workshop that tested a number of constructionist pedagogical approaches and one-to-one computing technology in a hypercontextualized storytelling workshop. In that workshop, which took place in a Tanzanian primary school, pupils used their XO-1 laptops as digital media tools for expressing their dreams and solutions to overcoming challenges in life. Results of this study suggest that digital storytelling offers additional advantages when compared to traditional storytelling. Designers need to follow six principles for a successful digital storytelling workshop: commitment, contextual grounding, previous exposure to the context, involvement of local experts, atmosphere of trust, and realistic flexible planning.
KerkoCite.ItemAlsoKnownAs: 2339240:RY6T9AGL 2405685:KW2JCTF6
Keywords: ⛔ No DOI found

School-based professional development in one Lebanese school: how much is too much? - Nabhani, Mona; Bahous, Rima; Hamdan, Zeina (Professional Development in Education, 2012)
This case study examines the attitudes of the secondary and middle school teachers at one school in Lebanon regarding the effect of the school’s professional development (PD) programs on the quality of their teaching practices and motivation. It also examines teachers’ attitudes regarding PD as well as their recommendations to improve the quality of the PD program provided by their school. Questionnaires, focus group interviews and observations were conducted to collect and triangulate data results. Results show that teachers regard PD in their school as beneficial in general but able to be enhanced further. Although the attitude of novice teachers towards PD is more favorable than that of veteran teachers, findings show that the overall teachers’ attitude towards PD is a negative one. Modifications and suggestions to improve the quality of the PD activities are proposed by the teachers. The school offers a prosperous PD program, but its fruitfulness will remain limited unless an organizational structure is created.
shortDOI: 10/fzxm7p KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2011.639077 10/fzxm7p 2339240:9WFGU8AX 2339240:WLWXRWJ2 2405685:DMXQEDYG 2405685:I8KIIXIE
Keywords: Lebanon; professional development; schools; ⛔ No DOI found